Study on Positive and Negative Signs in Chronic Schizophrenic Women - Sahel Hemmati (University of Social Welfare and Rehabilitation Sciences, 2002)
Objective: Schizophrenia has different clinical manifestations, although, it is one disorder patients divided to two groups type 1 and type 2. type 1 who have positive and type 2 who have negative signs. Materials & Methods: They have chronic schizophrenia and treated at least with one antipsychotic drug. With checklist the signs were controlled. Results: In these chronic patients, hallucinations (positive sign) are seen with almost all of negative signs. In the other hand, (1) Flat affect (2) A logia & volition (3) Social inattentiveness (4) Inability to feel intimacy are seen more than another signs. Conclusion: For these above  patients new antipsychotic must be examined.